High-entropy alloy material with uniform and tiny precipitation of Ag as well as preparation method and application of high-entropy alloy material

By designing Ag uniform and micro-precipitated high-entropy alloy materials, the friction wear and corrosion problems caused by large-size segregation of Ag elements in high temperature and marine medical environments are solved, and good anti-wear lubrication and antibacterial properties are achieved.

CN119392081APending Publication Date: 2025-02-07LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411526584.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In high temperature and marine medical environments, due to the large-size segregation problem of Ag elements, alloy materials have severe friction and wear at 400°C, and severe local corrosion of the solution occurs in the microbial environment, deteriorating the mechanical properties.

Method used

By designing Ag uniform micro-precipitation high-entropy alloy material CoCrFeNiZrxAgy, where x=0.3~0.6, y=0.1~0.3, it is prepared by sintering method to achieve uniform dispersion and decomposition of Ag elements, avoiding large-sized local segregation.

Benefits of technology

It achieved good anti-wear lubrication performance at 400℃, with a friction coefficient below 0.35 and a wear rate below 9×10-5Nm/mm3. It also showed excellent antibacterial effects in the field of marine medical care, with a high antibacterial rate on E. coli at 95%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392081A_ABST
    Figure CN119392081A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of high-performance metal materials, and particularly relates to an Ag uniform and tiny precipitation high-entropy alloy material and a preparation method and application thereof. According to the high-entropy alloy material with the Ag evenly and slightly separated out, according to the atomic ratio, the component of the high-entropy alloy material with the Ag evenly and slightly separated out is CoCrFeNiZrxAgy, x ranges from 0.3 to 0.6, and y ranges from 0.1 to 0.3; the Ag-rich solid solution comprises a solid solution matrix and tiny granular Ag-rich phases which are uniformly dispersed and distributed in the solid solution matrix. A simple and low-cost sintering method is adopted, an alloy block material with uniform and tiny precipitation of Ag is obtained, and good wear resistance and lubrication are achieved at the blind spot temperature of 400 DEG C; and the excellent antibacterial effect of the alloy is realized. The preparation process is simple and convenient, and is suitable for large-scale production, and the prepared alloy has important application prospects in the fields of high temperature and marine medical treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of high-performance metal materials, and in particular relates to a Ag uniform micro-precipitation high-entropy alloy material and a preparation method and application thereof. Background Art

[0002] In extreme service environments, the protective properties of alloy materials directly determine the service stability, reliability and service life of alloys and components. In high temperature environments, alloys undergo severe oxidation wear, resulting in severe friction, and lubrication modification is necessary. In marine and medical environments, alloys face microbial erosion, which causes premature failure of the alloys and increases the running resistance of components, so antibacterial modification is necessary. The research and development of high-performance protective metal materials in extreme environments has become a key task in international manufacturing competition.

[0003] Ag is the preferred modifying element for high-temperature lubrication of alloy materials and antibacterial properties in marine medical applications. Ag itself has a relatively low shear strength and can form a friction-reducing layer on the friction surface within the range of room temperature to 400°C, exerting an excellent lubricating effect. At the same time, Ag has an antibacterial effect superior to Cu, and has excellent contact sterilization and ion-release sterilization effects on bacteria and algae. Adding Ag to alloys is an effective means to improve the lubrication properties of alloys at high temperatures and the antibacterial properties in marine medical environments, and is a method commonly recognized by the field of metallurgy at home and abroad.

[0004] However, due to its low melting point and chemical inertness, adding Ag to most alloys will cause obvious large-scale segregation of Ag. For example, when using the smelting method, the Ag element and the alloy matrix are layered up and down; when using sintering methods such as hot pressing and SPS, the Ag element presents segregation with a length of more than tens of microns. The large-scale segregation of Ag will aggravate the softening of the alloy at high temperatures, resulting in severe friction and wear of most alloy materials reported at 400°C, which is a common problem in the research and development of high-temperature anti-wear lubricating alloy materials; it causes most alloy materials to suffer from severe solution local corrosion and deterioration of mechanical properties in a microbial environment. Regulating the distribution form of the Ag element in the alloy is very necessary to improve the protective performance of the alloy. Summary of the invention

[0005] The purpose of the present invention is to provide a Ag uniform micro-precipitation high entropy alloy material and its preparation method and application. The Ag uniform micro-precipitation high entropy alloy material provided by the present invention achieves good anti-wear lubrication at the blind spot temperature of 400°C; and achieves excellent antibacterial effect of the alloy. At the same time, the preparation method is simple and convenient, suitable for large-scale production, and the prepared alloy has important application prospects in high temperature and marine medical fields.

[0006] In order to achieve the above object, the present invention provides the following technical solutions:

[0007] The present invention provides a high entropy alloy material with uniform and micro-precipitated Ag. The composition of the high entropy alloy material with uniform and micro-precipitated Ag is CoCrFeNiZrxAgy, where x=0.3-0.6 and y=0.1-0.3, calculated by atomic ratio.

[0008] The Ag uniform micro-precipitation high-entropy alloy material comprises a solid solution matrix and a micro-granular precipitation phase uniformly dispersed in the solid solution matrix. The micro-granular precipitation phase is an Ag-rich phase, and the size of the micro-granular precipitation phase is ≤1 μm.

[0009] Preferably, the size of the micro-granular precipitated phase is less than 0.7 μm.

[0010] The present invention provides a method for preparing the Ag uniform micro-precipitation high entropy alloy material described in the above technical solution, comprising the following steps:

[0011] Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder are mixed according to atomic ratio to obtain mixed metal powder;

[0012] The mixed metal powder is sintered to obtain the Ag uniformly finely precipitated high entropy alloy material.

[0013] Preferably, the purity of the Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder is independently >99.5%.

[0014] Preferably, the particle sizes of the Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder are independently 1 to 60 μm.

[0015] Preferably, the mixing is carried out in a protective gas atmosphere, and the mixing is ball milling; the ball-to-material ratio of the ball milling is 1 to 3:1, the rotation speed is 150 to 400 r / min, and the time is 5 to 24 h.

[0016] Preferably, the ball milling is wet ball milling; the grinding medium of the wet ball milling is ethanol, and the ratio of the total mass of the Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder to the volume of the grinding medium is 100g: (1-5)mL;

[0017] The wet ball milling obtains ball milled wet powder, and the wet ball milling further comprises: drying the ball milled wet powder to obtain the mixed metal powder.

[0018] Preferably, the sintering is spark plasma sintering, and the sintering is carried out in a vacuum environment with a vacuum degree of 5×10 -3 ~1×10 -1 Pa.

[0019] Preferably, the sintering pressure is 20-50 MPa, the holding temperature is 1100-1300° C., the holding time is 5-15 min, and the heating rate from room temperature to the sintering holding temperature is 60-200° C. / min.

[0020] The present invention provides the use of the Ag uniform micro-precipitation high-entropy alloy material described in the above technical scheme or the Ag uniform micro-precipitation high-entropy alloy material prepared by the preparation method described in the above technical scheme as a wear-resistant lubricating material or an antibacterial material.

[0021] The present invention provides a Ag uniform micro-precipitation high entropy alloy material. According to the atomic ratio, the composition of the Ag uniform micro-precipitation high entropy alloy material is CoCrFeNiZrxAgy, wherein x=0.3-0.6, y=0.1-0.3; the Ag uniform micro-precipitation high entropy alloy material comprises a solid solution matrix and a micro-granular precipitation phase uniformly dispersed in the solid solution matrix, the micro-granular precipitation phase is an Ag-rich phase, and the size of the micro-granular precipitation phase is ≤1 μm. The present invention adopts a design method for high entropy alloys, and by reasonably setting the types of elements in the alloy and the atomic ratio relationship, the matrix is ​​realized as a solid solution structure with excellent mechanical properties, and at the same time, the uniform dispersion precipitation of micro-granular Ag-rich phase is realized, thereby avoiding large-scale local segregation of Ag. The Ag uniform micro-precipitation alloy block material provided by the present invention realizes good anti-wear lubrication at 400°C; and realizes the excellent antibacterial effect of the alloy, and has important application prospects in the fields of high temperature and marine medicine. The results of the examples show that the Ag uniform micro-precipitation high entropy alloy material provided by the present invention has a friction coefficient lower than 0.35 and a wear rate lower than 9×10 -5 Nm / mm 3 Compared with stainless steel, the Ag uniform micro-precipitation high entropy alloy material provided by the present invention has an antibacterial rate against Escherichia coli higher than 95%.

[0022] The present invention provides a method for preparing a high entropy alloy material with uniform micro-precipitation of Ag as described in the above technical solution, comprising the following steps: mixing Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder according to an atomic ratio to obtain a mixed metal powder; sintering the mixed metal powder to obtain the high entropy alloy material with uniform micro-precipitation of Ag. The present invention adopts a simple and low-cost sintering method to obtain an alloy block material with uniform micro-precipitation of Ag; it has solved the common technical problems of high-temperature lubricating alloys in a breakthrough way, and has achieved good anti-wear lubrication at the blind spot temperature of 400°C; and has achieved the excellent antibacterial effect of the alloy. The preparation process of the present invention is simple and convenient, suitable for large-scale production, and the prepared alloy has important application prospects in the fields of high temperature and marine medicine.

[0023] Figure Description

[0024] Figure 1 This is the organizational structure of the CoCrFeNiZr0.4Ag0.2 high entropy alloy with uniform and tiny Ag precipitation in Example 1;

[0025] Figure 2 This is a scanning diagram of the Ag element composition in the CoCrFeNiZr0.4Ag0.2 high entropy alloy with uniform and tiny Ag precipitation in Example 1;

[0026] Figure 3 is the friction coefficient curve of the CoCrFeNiZr0.4Ag0.2 high entropy alloy with uniform and fine Ag precipitation at 400°C in Example 1;

[0027] Figure 4 This is a scanning image of the Ag element composition in the CoCrFeNiZr0.6Ag0.3 high entropy alloy with uniform and tiny Ag precipitation in Example 3;

[0028] Figure 5 This is a scanning diagram of the organizational structure and Ag element composition of the CoCrFeNi-10wt% Ag high entropy alloy in comparative example 1. DETAILED DESCRIPTION

[0029] The present invention provides a high entropy alloy material with uniform and micro-precipitated Ag. The composition of the high entropy alloy material with uniform and micro-precipitated Ag is CoCrFeNiZrxAgy, where x=0.3-0.6 and y=0.1-0.3, calculated by atomic ratio.

[0030] The Ag uniform micro-precipitation high-entropy alloy material comprises a solid solution matrix and a micro-granular precipitation phase uniformly dispersed in the solid solution matrix. The micro-granular precipitation phase is an Ag-rich phase, and the size of the micro-granular precipitation phase is ≤1 μm.

[0031] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.

[0032] In the present invention, the x in the composition CoCrFeNiZrxAgy of the Ag uniform fine precipitation high entropy alloy material is specifically 0.4, 0.3 or 0.6.

[0033] In the present invention, y in the composition CoCrFeNiZrxAgy of the Ag uniform fine precipitation high entropy alloy material is specifically 0.2, 0.1 or 0.3.

[0034] In the present invention, the size of the micro-granular precipitated phase is preferably less than 0.7 μm.

[0035] The present invention provides a method for preparing the Ag uniform micro-precipitation high entropy alloy material described in the above technical solution, comprising the following steps:

[0036] Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder are mixed according to atomic ratio to obtain mixed metal powder;

[0037] The mixed metal powder is sintered to obtain the Ag uniformly finely precipitated high entropy alloy material.

[0038] The present invention mixes Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder according to atomic ratio to obtain mixed metal powder.

[0039] In the present invention, the purity of the Co powder is >99.5%. The particle size of the Co powder is preferably 1 to 60 μm. The purity of the Cr powder is >99.5%. The particle size of the Cr powder is preferably 1 to 60 μm. The purity of the Fe powder is >99.5%. The particle size of the Fe powder is preferably 1 to 60 μm. The purity of the Ni powder is >99.5%. The particle size of the Ni powder is preferably 1 to 60 μm. The purity of the Zr powder is >99.5%. The particle size of the Zr powder is preferably 1 to 60 μm. The purity of the Ag powder is >99.5%. The particle size of the Ag powder is preferably 1 to 60 μm.

[0040] In the present invention, the mixing is preferably carried out in a protective gas atmosphere, and the protective gas is preferably an inert gas, specifically preferably argon. The mixing is preferably ball milling. The ball milling jar used in the ball milling is preferably a stainless steel ball milling jar. The grinding beads used in the ball milling are preferably stainless steel balls. The ball-to-material ratio of the ball milling is preferably 1 to 3:1, and specifically 2:1, 3:1 or 1:1 in the embodiment. The rotation speed of the ball mill is preferably 150 to 400 r / min, and specifically 400 r / min, 150 r / min or 300 r / min in the embodiment. The time of the ball milling is preferably 5 to 24 h, and specifically 15 h, 24 h or 5 h in the embodiment. In the present invention, the ball milling is preferably wet ball milling; the grinding medium of the wet ball milling is preferably ethanol, and the ratio of the total mass of the Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder to the volume of the grinding medium is preferably 100g:(1-5)mL, specifically 100g:1mL, 100g:3mL or 100g:5mL in the embodiments.

[0041] In the present invention, when the mixing is preferably wet ball milling, the wet ball milling obtains ball milled wet powder, and after obtaining the ball milled wet powder, the present invention preferably further comprises drying the ball milled wet powder to obtain the mixed metal powder. The present invention has no special requirements for the specific implementation of the drying.

[0042] After obtaining the mixed metal powder, the present invention sintered the mixed metal powder to obtain the Ag uniform micro-precipitation high entropy alloy material.

[0043] The present invention preferably places the mixed metal powder into a mold and then sintering the mixed metal powder. The mold is preferably a graphite mold. In the present invention, the sintering is preferably spark plasma (SPS) sintering, and the sintering is preferably carried out in an SPS sintering furnace. The sintering is preferably carried out in a vacuum environment, and the vacuum degree is preferably 5×10 -3 ~1×10 -1 Pa, specifically 1×10 -1 Pa, 5×10 -3 Pa or 7×10 -3 Pa. The sintering pressure is preferably 20-50MPa, specifically 50MPa, 20MPa or 35MPa in the embodiments. The sintering insulation temperature is preferably 1100-1300°C, specifically 1300°C, 1100°C or 1200°C in the embodiments. The sintering insulation time is 5-15min, specifically 5min, 15min or 8min in the embodiments. The heating rate from room temperature to the sintering insulation temperature is 60-200°C / min, specifically 60°C / min, 200°C / min or 100°C / min in the embodiments. In a specific embodiment of the present invention, the specific implementation method of the sintering preferably includes: loading the mixed metal powder into a mold, placing it in an SPS sintering furnace, washing the furnace with an inert gas before sintering, then vacuuming, pressurizing, heating at the above heating rate, heating to the sintering insulation temperature, and then sintering at a temperature of sintering, and after sintering, cooling the material to room temperature with the furnace to obtain a high entropy alloy material with uniform and tiny precipitation of Ag. The inert gas used for washing the furnace is preferably argon.

[0044] The present invention provides the use of the Ag uniform micro-precipitation high-entropy alloy material described in the above technical scheme or the Ag uniform micro-precipitation high-entropy alloy material prepared by the preparation method described in the above technical scheme as a wear-resistant lubricating material or an antibacterial material.

[0045] In the present invention, the Ag uniform micro-precipitation high entropy alloy material is preferably used as a wear-resistant lubricating material or an antibacterial material in marine engineering or medical engineering.

[0046] The Ag uniform micro-precipitation high entropy alloy material provided by the present invention can be applied in a high-temperature environment, wherein the temperature of the high-temperature environment is room temperature to 400°C.

[0047] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] In the following embodiments of the present invention:

[0049] The microstructure and morphology of the alloy material were characterized by scanning electron microscopy (SEM). In order to evaluate the tribological properties of the alloy, a high temperature friction tester was used, and the alloy surface was polished to 2000# sandpaper. Al2O3 was used as the grinding material, the experimental temperature was 400℃, the load was 8N, the sliding rate was 0.15m / s, the sliding time was 30min, and the wear volume was analyzed by a three-dimensional profiler after the test, and the wear rate was calculated. In order to evaluate the antibacterial properties of the alloy, Escherichia coli (E.coli, ATCC) was used to carry out an antibacterial test in nutrient solution agar medium. For comparison, a similar antibacterial performance test was performed on the 304ss control sample. The polished sample was placed in a 12-well culture plate. A concentration level of 10 5 Drop a bacterial suspension of CFU / mL on the surface of the polished sample. Place the culture plate in an incubator at 37℃±1℃ and incubate for 24h. After incubation, remove the biofilm adhering to the surface and collect the planktonic bacteria from the solution. Dilute the biofilm and planktonic bacteria. Take 50μm of each dilution and culture it on nutrient solution agar medium in a constant temperature incubator at 37℃±1℃ for 24h, and count the number of bacteria.

[0050] Example 1

[0051] This embodiment provides a method for preparing a CoCrFeNiZr0.4Ag0.2 high entropy alloy material with uniform and fine Ag precipitation, and the steps are as follows:

[0052] Weighing materials: Weigh Co, Cr, Fe, Ni, Zr, and Ag powder materials according to the atomic ratio of the composition of CoCrFeNiZr0.4Ag0.2 high entropy alloy; the purity of Co, Cr, Fe, Ni, Zr, and Ag powder materials is >99.5%, and the particle size is 1-60 μm;

[0053] Ball milling: The weighed metal powder is loaded into a stainless steel ball mill and ball milled under an argon protective gas environment; 3 mL of anhydrous ethanol is added as a grinding medium for every 100 g of mixed powder, and the materials are mixed under an argon protective gas environment. The grinding balls are stainless steel balls, the ball mill is made of stainless steel, the ball-to-material ratio is 2:1, the ball mill speed is 300 r / min, and the ball milling time is 15 h; after ball milling, it is dried to obtain a uniformly mixed powder product.

[0054] Sintering: The obtained powder product was loaded into a graphite mold and then placed in an SPS spark plasma sintering furnace for sintering under vacuum. The sintering temperature was 1200°C. The furnace was washed with argon protective gas before sintering. The heating rate was 100°C / min, the sintering pressure was 35MPa, the holding time was 8min, and the vacuum degree was 7×10 -3 Pa; After sintering, the material is cooled to room temperature with the furnace to obtain a CoCrFeNiZr0.4Ag0.2 high entropy alloy material with uniform and fine Ag precipitation.

[0055] See also Figure 1 , the CoCrFeNiZr0.4Ag0.2 high entropy alloy obtained in this embodiment was subjected to microstructure analysis, and the Ag element was dispersed in the alloy in a uniform, granular form with a size less than 0.7 μm (the white dots were Ag-rich phases); Figure 2 , the CoCrFeNiZr0.4Ag0.2 high entropy alloy obtained in this embodiment is subjected to composition plane scanning, and the Ag element is dispersed in the alloy in a uniform, granular form with a size less than 0.7 μm; see Figure 3 The CoCrFeNiZr0.4Ag0.2 high entropy alloy obtained in this embodiment was subjected to a high temperature friction test at 400°C. The friction coefficient was lower than 0.35 and the wear rate was 7.9×10 -5 mm 3 / Nm; The CoCrFeNiZr0.4Ag0.2 high entropy alloy obtained in this embodiment was subjected to an antibacterial experiment. Compared with 304 stainless steel (304ss), the Ag uniform micro-precipitation high entropy alloy material prepared in this embodiment had an antibacterial rate against Escherichia coli higher than 95%.

[0056] Example 2

[0057] The present invention provides a method for preparing a CoCrFeNiZr0.3Ag0.1 high entropy alloy material with uniform and minute Ag precipitation, the steps of which are as follows:

[0058] Weighing materials: Weigh Co, Cr, Fe, Ni, Zr, and Ag powder materials of CoCrFeNiZr0.3Ag0.1 high entropy alloy according to the atomic ratio; the purity of Co, Cr, Fe, Ni, Zr, and Ag powder materials is >99.5%, and the particle size is 1-60 μm;

[0059] Ball milling: The weighed metal powder is loaded into a stainless steel ball mill and ball milled under an argon protective gas environment; 1 mL of anhydrous ethanol is added as a grinding medium for every 100 g of mixed powder, and the materials are mixed under an argon protective gas environment. The grinding balls are stainless steel balls, the ball mill is made of stainless steel, the ball-to-material ratio is 3:1, the ball mill speed is 150 r / min, and the ball mill time is 24 h; after ball milling, it is dried to obtain a uniformly mixed powder product.

[0060] Sintering: The obtained powder product was loaded into a graphite mold and then placed in an SPS spark plasma sintering furnace for sintering under vacuum. The sintering temperature was 1100°C, and the furnace was washed with argon protective gas before sintering. The heating rate was 200°C / min, the sintering pressure was 20 MPa, the holding time was 15 min, and the vacuum degree was 5×10 -3 Pa; After sintering, the material is cooled to room temperature along with the furnace to obtain a CoCrFeNiZr0.3Ag0.1 high entropy alloy material with uniform and fine Ag precipitation.

[0061] The composition surface scanning of the CoCrFeNiZr0.3Ag0.1 high entropy alloy obtained in this embodiment shows that the Ag element is evenly dispersed in the alloy with a size of less than 0.5 μm. The high-temperature friction test of the CoCrFeNiZr0.3Ag0.1 high entropy alloy obtained in this embodiment is carried out at 400°C. The friction coefficient is less than 0.35 and the wear rate is 9.0×10 -5 mm 3 / Nm; The CoCrFeNiZr0.3Ag0.1 high entropy alloy obtained in this embodiment was subjected to an antibacterial experiment. Compared with 304 stainless steel (304ss), the Ag uniform micro-precipitation high entropy alloy material prepared in this embodiment had an antibacterial rate against Escherichia coli higher than 95%.

[0062] Example 3

[0063] This embodiment provides a method for preparing a CoCrFeNiZr0.6Ag0.3 high entropy alloy material with uniform and fine Ag precipitation, and the steps are as follows:

[0064] Weighing materials: weigh Co, Cr, Fe, Ni, Zr, and Ag powder materials according to the atomic ratio of CoCrFeNiZr0.6Ag0.3 high entropy alloy components; the purity of Co, Cr, Fe, Ni, Zr, and Ag powder materials is >99.5%, and the particle size is 1-60 μm;

[0065] Ball milling: The weighed metal powder is loaded into a stainless steel ball mill and ball milled under an argon protective gas environment; 5 mL of anhydrous ethanol is added as a grinding medium for every 100 g of mixed powder, and the materials are mixed under an argon protective gas environment. The grinding balls are stainless steel balls, the ball mill is made of stainless steel, the ball-to-material ratio is 1:1, the ball mill speed is 400 r / min, and the ball milling time is 5 h; after ball milling, it is dried to obtain a uniformly mixed powder product.

[0066] Sintering: The obtained powder product was loaded into a graphite mold and then placed in an SPS spark plasma sintering furnace for sintering under vacuum. The sintering temperature was 1300°C, and the furnace was washed with argon protective gas before sintering. The heating rate was 60°C / min, the sintering pressure was 50MPa, the holding time was 5min, and the vacuum degree was 1×10 -1 Pa; After the sintering is completed, the material is cooled to room temperature with the furnace to obtain a CoCrFeNiZr0.6Ag0.3 high entropy alloy material with uniform and fine Ag precipitation.

[0067] See also Figure 4 The composition plane of the CoCrFeNiZr0.6Ag0.3 high entropy alloy obtained in this embodiment was scanned, and the Ag element was evenly dispersed in the alloy with a size of less than 0.7 μm. The CoCrFeNiZr0.6Ag0.3 high entropy alloy obtained in this embodiment was subjected to a 400°C high temperature friction test, and the friction coefficient was less than 0.35, and the wear rate was 7.3×10 -5 mm 3 / Nm; The CoCrFeNiZr0.6Ag0.3 high entropy alloy obtained in this embodiment was subjected to an antibacterial experiment. Compared with 304 stainless steel (304ss), the Ag uniform micro-precipitation high entropy alloy material prepared in this embodiment had an antibacterial rate against Escherichia coli higher than 95%.

[0068] Comparative Example 1

[0069] In order to verify the Ag precipitation structure advantages of the alloy of the present invention and the performance advantages provided by the Ag precipitation structure, a comparative example CoCrFeNi-10wt% Ag was designed, corresponding to CoCrFeNiAg0.23 in atomic ratio. The sintering process was as follows: sintering temperature was 1250℃, the furnace was washed with argon protective gas before sintering, the heating rate was 100℃ / min, the sintering pressure was 40MPa, the holding time was 15min, and the vacuum degree was 1×10 -1 Pa. See Figure 5 The CoCrFeNi-10wt%Ag high entropy alloy obtained by the comparison was scanned for its structure and composition, and the Ag element with a size of more than tens of microns was locally distributed in the intergranular region of the alloy, proving the advantage of the present invention in the Ag precipitation structure.

[0070] The same friction tester (HV-1000) was used to conduct tribological experiments under the same friction environment and conditions. The alloy surface was polished to 2000# sandpaper. Al2O3 was used as the grinding material. The experimental temperature was 400℃, the load was 8N, the sliding rate was 0.15m / s, and the sliding time was 30min. After the test, the wear volume was analyzed by a three-dimensional profiler and the wear rate was calculated. The friction coefficient of the alloy was 0.45 and the wear rate was 32×10 -5mm 3 / Nm.

[0071] Related results have been published in the paper (Microstructure, Mechanical, and Tribological Properties of CoCrFeNi-Ag-Mo Self-lubricating Composite. Journal of Materials Engineering and Performance, 2024, 33(4): 1704-1717), and the friction coefficient and wear rate are much higher than those of Examples 1, 2, and 3 of the present invention. This proves the advantage of the alloy of the present invention in tribological properties.

[0072] From the above examples, it can be seen that the present invention adopts the design method of high entropy alloy to realize the matrix as a solid solution structure with excellent mechanical properties; unexpectedly, the tiny uniform precipitation of Ag is achieved, avoiding the large-scale local segregation of Ag. Based on the tiny uniform precipitation structure of Ag, the prepared alloy has achieved the following breakthrough properties: at the blind spot temperature of 400℃ for high-temperature lubrication, the friction coefficient is less than 0.35, and the wear rate is less than 9×10 -5 Nm / mm 3 Compared with 304 stainless steel (304ss), the Ag uniform micro-precipitation high entropy alloy material provided by the present invention has an antibacterial rate against Escherichia coli higher than 95%.

[0073] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A high entropy alloy material with uniform micro-precipitation of Ag, characterized in that: According to the atomic ratio, the composition of the Ag uniform micro-precipitation high entropy alloy material is CoCrFeNiZrxAgy, wherein x=0.3-0.6, y=0.1-0.3; The Ag uniform micro-precipitation high-entropy alloy material comprises a solid solution matrix and a micro-granular precipitation phase uniformly dispersed in the solid solution matrix. The micro-granular precipitation phase is an Ag-rich phase, and the size of the micro-granular precipitation phase is ≤1 μm.

2. The Ag uniform micro-precipitation high entropy alloy material according to claim 1, characterized in that: The size of the micro-granular precipitated phase is less than 0.7 μm.

3. The method for preparing the Ag uniform micro-precipitation high entropy alloy material according to claim 1 or 2, characterized in that: The following steps are involved: Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder are mixed according to atomic ratio to obtain mixed metal powder; The mixed metal powder is sintered to obtain the Ag uniformly finely precipitated high entropy alloy material.

4. The preparation method according to claim 3, characterized in that: The purity of the Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder is independently greater than 99.5%.

5. The preparation method according to claim 3, characterized in that: The particle sizes of the Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder are independently 1 to 60 μm.

6. The preparation method according to any one of claims 3 to 5, characterized in that: The mixing is carried out in a protective gas atmosphere, and the mixing is ball milling; the ball-to-material ratio of the ball milling is 1-3:1, the rotation speed is 150-400 r / min, and the time is 5-24 hours.

7. The preparation method according to claim 6, characterized in that: The ball mill is a wet ball mill; the grinding medium of the wet ball mill is ethanol, and the ratio of the total mass of the Co powder, Cr powder, Fe powder, Ni powder, Zr powder and Ag powder to the volume of the grinding medium is 100g: (1-5)mL; The wet ball milling obtains ball milled wet powder, and the wet ball milling further comprises: drying the ball milled wet powder to obtain the mixed metal powder.

8. The preparation method according to claim 3, characterized in that: The sintering is spark plasma sintering, and the sintering is carried out in a vacuum environment with a vacuum degree of 5×10 -3 ~1×10 -1 Pa.

9. The preparation method according to claim 1 or 8, characterized in that: The sintering pressure is 20-50 MPa, the holding temperature is 1100-1300° C., the holding time is 5-15 min, and the heating rate from room temperature to the sintering holding temperature is 60-200° C. / min.

10. Use of the Ag uniform micro-precipitation high entropy alloy material according to claim 1 or 2 or the Ag uniform micro-precipitation high entropy alloy material prepared by the preparation method according to any one of claims 3 to 9 as a wear-resistant lubricating material or an antibacterial material.